On the origin of species - Darwin, Charles, 1809-1882 (Sterling, 2011)
This year marks the 150th anniversary of the publication of Charles Darwin's On the Origin of Species by Means of Natural Selection, or the Preservation of Favoured Races in the Struggle for Life. In his landmark study, Darwin theorised that populations evolve over the course of generations through a process of natural selection. These ideas flew in the face of long-held beliefs and the book immediately became one of the most controversial scientific works in history - and it still remains so today. Now, for the first time, Darwin's classic is fully and handsomely illustrated with over 350 illustrations and photographs, many of them in brilliant colour. Reproductions from Darwin's The Voyage of the Beagle appear throughout in addition to brief excerpts from his letters, diaries and correspondence - bringing both Darwin the man and his revolutionary discovery to life.